Gambaran Penggunaan Kontrasepsi Hormonal dan Kejadian Efek Samping Penggunaan Kontrasepsi Hormonal Pada Wanita Usia Subur - Lidia Aditama Putri; Nurun Nikmah (Universitas Muhammadiyah Gresik, 2021)
Hormonal contraceptive methods are considered one of the methods with a high level of effectiveness. Although it has high effectiveness, it doesn’t mean that hormonal contraceptives are without side effects. The purpose of this study was to describe the use of hormonal contraceptives and their side effects. This type of descriptive research was conducted in March-May 20201 at BPM Lilik Nur Hidayati, SST. A total of 80 hormonal family planning acceptors were selected by purposive sampling technique. Data collection was carried out by in-depth interview techniques using interview guidelines. Data analysis using frequency distribution table. The results of this study showed that out of 80 acceptors, almost all of them used 1-month injections (33.8%), followed by 3-month injections (25%), combined pills (12.5%), progestin pills (11 .3%), norplant type implant (10%), implanon type implant (3.7%), and jadena type implant (3.75). Meanwhile, the most frequent side effects experienced by the acceptors were weight gain (61.2%), followed by menstrual disorders (22.5%), gastrointestinal disorders (10%), the appearance of black spots (3.8%), and decreased libido (2.5%). The use of 1-month injectable contraceptives is the type of contraception that is most in demand by women of childbearing age, while the most common side effect is weight gain